UTILIZATION OF MULTIMEDIA TO IMPROVE PIT FISSURE SEALANT PRACTICAL SKILL AMONG STUDENTS IN DENTAL NURSING, YOGYAKARTA, INDONESIA - Wiworo Haryani; Maria Dewi Christiyawati; Yuni Kusmiyati; Waryana Waryana (Belitung Raya Foundation, Indonesia, 2016)
Background: With an increasing demand of high quality of health services, challenges are addressed to all health providers to improve their skills in providing services to clients. Given that preventive dentistry clinical practice has not been satisfying, providing media as students’ guidelines is necessary. Objective: The study aims to explain the influence of multimedia use in order to improve Pit Fissure Sealant (PFS) practical skills of dental nursing students. Methods: It was a quasi-experimental study with pretest and post-test control group design. Population of the study was selected from dental nursing students in Yogyakarta. A hundred sample was drawn purposively from the population and distributed equally to two groups. The first group was exposed by PFS practice video whilst the second group as control was exposed only by the guidebook. Results: Initially, students in the control group have better PFS practical score compared to their counterpart in the treatment group. Nevertheless, after the exposure of different media, students in the treatment group demonstrated a better post-test score on their PFS practical skills. The statistical analysis certifies that there was a significant difference in the mean score of PFS practical skills of the students before and after the treatment. Conclusion: Video as a new media is able to improve the students’ motivation in learning than any traditional media such as books. It should be noted however, both printed media (guidebooks) and video only provides one-way communication. Therefore, designing an interactive media using video, which the user can be the sender, not only the receiver, can be considered for further research.